Do parent media habits contribute to child global development? - Fitzpatrick, Caroline; Johnson, Alexa; Laurent, Angélique; Bégin, Mathieu; Harvey, Elizabeth (Frontiers in Psychology, 2024)
Background/Objective. Parents of preschoolers’ report using screen media frequently. More frequent screen use by parents may undermine child development by displacing time for foundational parent-child interactions. The objective of the present study is to examine the extent to which parent screen use contributes to child global development 1 year later. Methods: Data are from a cohort of 315 preschoolers from Nova Scotia, Canada and their parents during the COVID-19 pandemic. Parents reported the number of hours per day they spent using screens, as well as child screen time and sex, and parent educational attainment. Our outcome is child global development scores, which combine assessments of communication, cognitive, personal-social, and motor skills measured at 4.5 using the Ages and Stages Questionnaire (ASQ) (N=249, 79% retained). Results: Parents in our sample spent on average 6.35 hours per day using screen media outside of work (SD=3.07) and children spent on average 3.43 hours per/day using screens. Multivariate linear regression indicated that each 1-hour increase in parents daily screen media use, corresponded to a 1.25 decrease in child global development scores, B = -1.25 p <.05, 95% CI between -2.37 and -.13. Conclusion: Our results indicate that parent screen use may represent a key component of children’s media ecology. Given the importance of global development in early childhood for later health and achievement, the present results suggest that interventions should include parent screen use habits in media wellness interventions.